2015
DOI: 10.1136/jclinpath-2015-203130
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic value of putative cancer stem cell markers CD117 and CD15 in choroidal and ciliary body melanoma

Abstract: 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Several studies explored the KIT expression and its prognostic significance in UM [ 21 , 22 , 38 , 39 , 40 ]. KIT positivity, detected in 20 of 48 (41.7%) samples analyzed in our study, agrees to 54% positivity reported by Lukenda et al, using the identical >10% cutoff [ 21 ]. However, with a 50% cutoff, Lüke et al found high KIT expression in 63% of UM patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies explored the KIT expression and its prognostic significance in UM [ 21 , 22 , 38 , 39 , 40 ]. KIT positivity, detected in 20 of 48 (41.7%) samples analyzed in our study, agrees to 54% positivity reported by Lukenda et al, using the identical >10% cutoff [ 21 ]. However, with a 50% cutoff, Lüke et al found high KIT expression in 63% of UM patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 (Cyclin-D1-binding protein 1), Ki-67 (Proliferation marker protein Ki-67), and p53 (Cellular tumor antigen p53) positivities were linked with an unfavorable outcome [ 20 ]. Likewise, the overexpression of transmembrane tyrosine kinase receptor KIT (Mast/stem cell growth factor receptor Kit, alternative name CD117) was associated with poor prognosis in choroidal and ciliary body UM [ 21 , 22 ]. We recently identified 5-fold upregulation of its mRNA in M3 tumors compared to those with two copies of chromosome 3 (disomy 3, D3) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that stem cells have the ability of self-renewal, unlimited proliferation, drug resistance, high invasion and express high levels of CD117 and CD133 (18,19), we identified highly invasive populations of A2780 and A2780-PTX cells through Transwell assays. We screened the drug-resistant ovarian cancer cell line A2780-PTX for a highly drug-resistant ovarian cancer cell population with high invasiveness, and designated this population A2780-PTX-PM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, choroidal and ciliary body melanoma CSCs express CD117 and CD15 markers [88]. Overall, these studies suggest that tumors of various organs consist of distinct CSC populations with different stemness phenotypes.…”
Section: Manifold Existence Of Cancer Stem Cells and Its Impact On Camentioning
confidence: 99%
“…CD44 + and CD133 + cells have been proposed to be CSCs of medullary thyroid carcinoma [85], endometrial cancers [86] and rectal cancer [87]. In addition, choroidal and ciliary body melanoma CSCs express CD117 and CD15 markers [88]. Overall, these studies suggest that tumors of various organs consist of distinct CSC populations with different stemness phenotypes.…”
Section: Manifold Existence Of Cancer Stem Cells and Its Impact On Camentioning
confidence: 99%